Concurrent versus sequential immunotherapy with chemoradiotherapy for unresectable stage III non-small-cell lung cancer: a retrospective study - Meng-Xi, Zhou; Wen-Jie, Fan; Ning, Zhang; Li-Yang, Zhu; Hong-Yan, Wang (Frontiers in Oncology, 2025)
BackgroundImmunotherapy combined with chemoradiotherapy has demonstrated promising efficacy in stage III non-small-cell lung cancer (NSCLC). However, the optimal timing for immunotherapy intervention during radiotherapy remains unclear. This study aimed to compare the efficacy and safety of immune checkpoint inhibitors (ICIs) administered concurrently or sequentially with chemoradiotherapy in unresectable stage III NSCLC.MethodsA retrospective analysis of 98 patients with unresectable stage III NSCLC, treated between January 1, 2019, and June 30, 2023, was conducted. Patients were grouped based on concurrent or sequential administration of ICIs with chemoradiotherapy. Median progression-free survival (mPFS), median overall survival (mOS), 1 and 2-year PFS rates, 2 and 3-year OS rates, objective remission rate (ORR), and disease control rate (DCR) were evaluated. Survival analysis was performed using the Kaplan–Meier method. Univariate and multivariate analyses were conducted using the log-rank test and Cox proportional hazards model. Treatment-related adverse effects were assessed and graded.ResultsA total of 98 patients with unresectable stage III NSCLC treated with chemoradiotherapy and ICIs were included. The mPFS and mOS were 19.0 (14.2-23.8) months and 31.5 (24.3-38.7) months, 12.8 (9.5-16.1) months and 28.5 (19.3-37.7) months in the concurrent and sequential ICI groups, respectively, and mPFS showed a significant difference (P=0.047). The estimated 1 and 2-year PFS rates were 79.6% (95% confidence interval [CI]: 67.6-91.6) and 40.4% (95% CI: 15.8-49.2) for the concurrent group, compared to 51.0% (95% CI: 35.9-66.1) and 31.6% (95% CI: 14.5-48.7) for the sequential group. The estimated 2 and 3-year OS rates were 65.7% (95% confidence interval [CI]: 48.6-82.8) and 40.0% (95% CI: 16.1-63.9) for the concurrent group, compared to 54.6% (95% CI: 35.8-73.4) and 28.7% (95% CI: 4.8-52.6) for the sequential group. The Eastern Cooperative Oncology Group Performance Status Scale (ECOG) score and tumor differentiation were identified as independent factors associated with PFS and OS. Distant metastasis occurred in 13.8% and 25.5% of patients in the concurrent and sequential ICI groups, respectively (P=0.049). The incidence of any grade of pneumonitis was 43.1% and 38.3% in two groups, with grade 3 or higher in 7.8% and 8.5% of patients, respectively. Hematologic toxicity of any grade was observed in 29.4% and 34.0% of the two groups, with grade 3 or higher toxicity identified in 3.9% and 2.1% of patients, respectively.ConclusionsConcurrent immunotherapy combined with chemoradiotherapy demonstrated superior efficacy than sequential immunotherapy, with good safety and tolerability in patients with unresectable stage III NSCLC.